Evaluating Presence of Computer Vision Syndrome among Medical Students at Libyan International University through Symptom Analysis - Elsaid, Amina; AL- Orfi , Hamad; AL- Obidy, Esraa (AlQalam Journal of Medical and Applied Sciences, 2025)
Computer Vision Syndrome (CVS) is a group of eye and vision-related problems resulting from prolonged use of digital devices. With the increasing dependence on technology in education, especially among medical students, the prevalence of CVS has become a significant health concern. Understanding the prevalence and associated symptoms of CVS among medical students is essential for developing targeted preventive measures. The study aims to determine the prevalence of CVS among medical students at Libyan International University (LIU), and the commonly reported symptoms of CVS were examined. A cross-sectional survey was conducted among 250 medical students at LIU using a convenience sampling method. Data were collected via a self-administered English-language questionnaire. Out of 250 respondents, 109 were male, and 141 were female. The age groups ranged from 18 to 30 years. The study revealed that CVS neck or shoulder pain was the most common symptom (73.2%), followed by eye strain (72.8%), headaches (68%), blurred vision (60.8%), and itchy eyes (56%). This study concludes that students’ symptoms were highly probable for CVS. The prevalence of symptoms such as neck or shoulder pain, eye strain, and headaches is high. The CVS score was significantly associated with gender, with females at higher risk.